2018
DOI: 10.1155/2018/1383697
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic and Anti-Inflammatory Effects of Eupatorium japonicum Thunb. in Rheumatoid Arthritis Fibroblast-Like Synoviocytes

Abstract: Rheumatoid arthritis (RA) is a chronic autoimmune inflammatory disease characterized by synovitis, hyperplasia, and the destruction of bone and cartilage. A variety of immunosuppressive biological agents have been developed because the pathogenesis of RA is related predominantly to the inflammatory response. However, rheumatoid arthritis fibroblast-like synovial cells (RAFLS), which are known to play an important role in RA progression, exhibit resistance to immunosuppressants through cancer-like properties. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…All statistical tests were based on the normal (NC) group and TNFa (NC) group, respectively (*p \ 0.05; **p \ 0.01). All the data were presented as the mean ± SD of three independent experiments and FLSs from three donor were used joint and ultimately disability (Shin et al 2018). RA-FLSs display 'tumor-like' features, including increased migration, invasion and reduced apoptosis (Nakamura et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…All statistical tests were based on the normal (NC) group and TNFa (NC) group, respectively (*p \ 0.05; **p \ 0.01). All the data were presented as the mean ± SD of three independent experiments and FLSs from three donor were used joint and ultimately disability (Shin et al 2018). RA-FLSs display 'tumor-like' features, including increased migration, invasion and reduced apoptosis (Nakamura et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that DK-59 reduced cell viability and induced ROS production and apoptosis in MH7A cells via up-regulating ATF4 and CHOP, activating Caspase-7 and PARP, as well as increasing phosphorylation of eIF2α [120]. Similarly, the extracts of Eupatorium japonicum Thunb (EJTE, 37.5 µg/mL) also showed apoptosis inducing activities in RA-FLS via ERS-mediated apoptotic pathway, such as up-regulation of ATF4 and CHOP [121]. Another in vitro experiment by Lu et al showed that in the presence of H 2 O 2 , resveratrol (1) (50-400 µM) could induce the apoptosis in FLS with a dose-dependent manner.…”
Section: Ers Mediated Apoptotic Pathwaymentioning
confidence: 96%
“…According to reactivity towards the earlier mentioned DHPAs, the MAb 4B8‐based icELISA detected an amount of cross‐reactive compounds in samples of Senecio vulgaris and E. japonicum that previously had no MCT content reported. Positive results were obtained due to its CR against senecionine and retrorsine in Senecio vulgaris or MCT‐related pyrrolizidine alkaloids in E. japonicum . The high contents of these compounds in Senecio vulgaris and E. japonicum produced positive results in the Mab 4B8‐based icELISA.…”
Section: Resultsmentioning
confidence: 99%